2018
DOI: 10.3310/hta22460
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of extravasation injuries in infants and young children: a scoping review and survey

Abstract: BackgroundExtravasation injuries are caused by unintended leakages of fluids or medicines from intravenous lines, but there is no consensus on the best treatment approaches.ObjectivesTo identify which treatments may be best for treating extravasation injuries in infants and young children.DesignScoping review and survey of practice.PopulationChildren aged < 18 years with extravasation injuries and NHS staff who treat children with extravasation injuries.InterventionsAny treatment for extravasation injury.Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 158 publications
0
29
0
5
Order By: Relevance
“…Uncertainty remains over whether there is a difference in the outcomes of children who are treated conservatively or surgically and the case series that exist on conservative management cover a number of treatments for a range of injuries from swelling to full-thickness defects. However, a recent scoping review found that the outcomes used and results detailed were generally limited, 6 making it difficult for clinicians to rely on those studies in deciding who to treat conservatively. This is why we have focused solely on studies describing invasive interventions: the Gault technique, debridement and further surgery, and hyaluronidase injections.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainty remains over whether there is a difference in the outcomes of children who are treated conservatively or surgically and the case series that exist on conservative management cover a number of treatments for a range of injuries from swelling to full-thickness defects. However, a recent scoping review found that the outcomes used and results detailed were generally limited, 6 making it difficult for clinicians to rely on those studies in deciding who to treat conservatively. This is why we have focused solely on studies describing invasive interventions: the Gault technique, debridement and further surgery, and hyaluronidase injections.…”
Section: Interventionsmentioning
confidence: 99%
“…It is therefore not known which of these treatments are effective, harmful or at the very least, necessary; a conclusion supported by a recent scoping review of interventions. 6 That review highlighted the fact that the lack of consensus extended to published guidelines. Their survey also showed wide variation in the frequency of use of the saline washout techniques in neonatal units across the National Health Service in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty remains over whether there is a difference in the outcomes of children who are treated conservatively or surgically and the case series that exist cover a number of treatments for a range of injuries from swelling to full-thickness defects. However, a recent scoping review found that the outcomes used and results detailed were generally limited, 6 making it difficult for clinicians to rely upon those studies in deciding who to treat conservatively. This is why we have focused solely on surgical interventions.…”
Section: Interventionsmentioning
confidence: 99%
“…It is therefore not known which of these treatments are effective, harmful or at the very least, necessary; a conclusion supported by a recent scoping review of interventions. 6 That review highlighted the fact that the lack of consensus extended to published guidelines. Their survey also showed wide variation in the frequency of use of the saline washout techniques in neonatal units across the National Health Service (NHS) in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents a more succinct account of a study of treatments for extravasation injuries in infants and children which has also been reported in full as an NIHR HTA report. [1]…”
Section: Introductionmentioning
confidence: 99%